The interpersonal effect of guilt expressions on cooperation: The role of social perceptions - MELIA, Nadhilla Velda (Institutional Knowledge at Singapore Management University, 2018)
People can make inferences about an individual based on his or her emotional expressions, and these inferences can affect their subsequent behavior. I conducted two experiments to investigate the social perceptions associated with a transgressor’s guilt expression after he or she commits a social transgression, and how these would subsequently affect the cooperative behavior of the victims of the transgression. Study 1 demonstrated that there was an indirect effect of a transgressor’s guilt expression on a victim’s cooperation via the victim’s perception of the transgressor’s benevolence, but not via the victim’s perception of the transgressor’s perspective-taking. Study 2 showed partial support for an indirect effect of a transgressor’s benevolence, but not a transgressor’s perspective-taking, on a victim’s cooperation via the victim’s perception of the transgressor’s guilt emotions. The results also suggest a bidirectional relationship between a victim’s perceptions of a transgressor’s guilt and benevolence, such that one can be inferred from the other. This research suggests the mechanisms regarding the appeasement function of guilt (i.e. through social perceptions) and illustrates how relationships may be repaired after a social transgression by examining social transgressions from the perspective of the victim, rather than the transgressor.